2022
DOI: 10.3390/biomedicines10051129
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk from Non-Obese Women with a High Omega-6 to Omega-3 Fatty Acid Ratio, but Not from Women with Obesity, Increases Lipogenic Gene Expression in 3T3-L1 Preadipocytes, Suggesting Adipocyte Dysfunction

Abstract: Maternal body mass index is associated with breast milk (BM) fatty acid composition. This study investigated the effects of BM omega (n)-6:n-3 polyunsaturated fatty acids (PUFAs) from non-obese women and women with obesity on the process of adipogenesis in 3T3-L1 preadipocytes. BM samples were collected from non-obese women (BMNO) and women with obesity (BMO) at one month postpartum. The fatty acid composition was measured, and BMNO and BMO groups with the lowest (Q1) and highest (Q4) quartiles of n-6:n-3 PUFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…In our study, nBMI breast milk samples had significantly lower (23.8%) LA levels than the nBMI+GD (25.8%), O (26.8%), and O+GD (27.8%) samples. Similar to Isesele et al [ 72 ], we found no significant differences in AA levels between the normal and obese BMI groups, implying that maternal obesity has little effect on AA levels. However, a small amount of GLA metabolite (˂0.3%) was found in the nBMI and nBMI+GD breast milk samples.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, nBMI breast milk samples had significantly lower (23.8%) LA levels than the nBMI+GD (25.8%), O (26.8%), and O+GD (27.8%) samples. Similar to Isesele et al [ 72 ], we found no significant differences in AA levels between the normal and obese BMI groups, implying that maternal obesity has little effect on AA levels. However, a small amount of GLA metabolite (˂0.3%) was found in the nBMI and nBMI+GD breast milk samples.…”
Section: Discussionsupporting
confidence: 89%
“…GLA showed a steady rise between transitional and mature milk, while linoleic acid, EPA, and ALA remained relatively stable. Isesele et al [ 72 ] found that obese women had higher levels of LA than non-obese women. LA is the precursor for AA, and it is converted to AA through a series of delta-6 desaturation, elongation, and delta-5 desaturase reactions [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid network further analysis revealed that C18:0 and C18:1 was significantly higher in non-obese mothers at both post-partum one and four and C12, C14, and C10 were significantly higher in obese mothers' breast milk, compared to non-obese mothers' breast milk. These trends with plasmalogen C18:0 and C18:1 levels were confirmed by applying different computational approaches to the same dataset 7,27 .…”
Section: Discussionmentioning
confidence: 62%
“…The human cross-sectional study showed that the triglyceride concentration was significantly higher in obese mothers' serum compared to normal-weight mothers' serum, but they did not show any significant difference in colostrum 29 . Obese mothers showed high levels of palmitic acid, dihomo-gamma-linolenic acid (DGLA), omega 6 polyunsaturated fatty acid, and adrenic acid and low levels of oleic acid and conjugated linoleic acid in their breast milk 27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive energy intake can result in fatty acid denaturation and lipid buildup in the liver. A low ratio of LA/ALA intake prevented adipocyte hypertrophy and reduced obesity [27,28]. In mice fed a high-fat diet containing a low ratio of LA/ALA, we observed a significant increase in the antioxidant capacity of the liver and a decrease in TG and TC levels in the liver.…”
Section: Discussionmentioning
confidence: 71%